2000
DOI: 10.1136/adc.83.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Parental smoking, socioeconomic factors, and risk of invasive meningococcal disease in children: a population based case-control study

Abstract: Aims-To investigate the eVects of parental smoking, socioeconomic characteristics, and indoor environment on the risk of invasive meningococcal disease in children. Methods-Population based case-control study. A total of 68 incident cases of invasive meningococcal disease in children less than 15 years old were compared with 135 controls selected from the same school and matched for year of birth, sex, and place of residence. Information on exposures was obtained in interviews with parents. Results-Invasive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 21 publications
5
44
0
7
Order By: Relevance
“…This is in accordance with a study done in Brazil that reported the frequency of the illness was around two times higher in low financial zones than in more prosperous zones [12].…”
Section: Parental Demographic Characteristicssupporting
confidence: 81%
“…This is in accordance with a study done in Brazil that reported the frequency of the illness was around two times higher in low financial zones than in more prosperous zones [12].…”
Section: Parental Demographic Characteristicssupporting
confidence: 81%
“…A educação da mãe é um forte preditor da saúde da criança, o que vem reforçar a idéia de que talvez esse fator seja o mais importante determinante sócio-econômico das condições de saú-de e doença da criança 30,31 . Mães mais escolarizadas podem mudar seu hábito de fumar ou adotar padrões comportamentais em relação ao fumo diferentes daquelas de menor escolaridade, como, por exemplo, não fumar dentro de casa, não fumar na presença dos filhos, impedir que outros moradores fumem na presença das crianças, por saber que esta atitude pode prejudicar a saúde infantil.…”
Section: Discussionunclassified
“…• invasive meningitis, 200,201 • infection with Mycobacterium tuberculosis in children who live in a household with a patient with tuberculosis, 202 and…”
Section: Effects On the Child Of Shs Exposurementioning
confidence: 99%